Using The Hello Talk Application To Improve The Arabic Language Ability Of Early Children - Sunarko, Asep; Hapsari, Ameilia Frida Putri; Fadil, M Zainul (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
The purpose of this study is to determine the extent to which the hello talk application helps users develop Arabic language skills, both in the aspects of listening, speaking, reading, or writing. And provide advice to Arabic language learners in utilizing this application optimally in order to improve their abilities, especially among the younger generation who are familiar with technology. The method used in this research is qualitative descriptive in which data is obtained using indirect interview techniques through research instruments in the form of guided interview questions to users of the hello talk application who are learning Arabic. And data analysis is done with several stages according to miles and Huberman. The results showed that the use of the hello talk application for Arabic language learning showed significant potential, especially in reading, writing and speaking skills.